Preparation method of conductive substance modification material layer, conductive glass electrode, conductive glass and dynamic window

CN119461887AActive Publication Date: 2025-02-18GUANGDONG UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411454755.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18
Estimated Expiration
2044-10-17

Smart Images

  • Figure CN119461887A_ABST
    Figure CN119461887A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of conductive materials and electrochromism, in particular to a preparation method of a conductive substance modification material layer, a conductive glass electrode, conductive glass and a dynamic window. Palladium ions serving as a catalyst are finally adsorbed through the polymer layer, a more uniform catalyst layer can be formed on the surface, the voltage difference between the center and the edge of the Pd-ITO conducting layer can be effectively reduced, the metal deposition effect is good, transparent and opaque state conversion can be well achieved, and metal in the center and the edge is uniformly and rapidly deposited. In addition, the problems of raw material agglomeration and instability can be avoided, and the preparation method has the advantages of low raw material cost, short preparation time, high preparation efficiency, simple and rapid process and facilitation of commercialization, and can be well applied as an electro-glass electrode and applied to preparation of conductive glass and dynamic windows.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive materials and electrochromic technology, and in particular to a method for preparing a conductive substance modified material layer, a conductive glass electrode, conductive glass and a dynamic window. Background Art

[0002] Dynamic windows are a type of window technology that can automatically adjust light transmittance according to environmental changes. This type of window can switch between transparent and opaque states within one minute. It is mainly composed of two pieces of glass sandwiching a conductive material, and the light transmittance of the material is controlled by electric current. Dynamic windows have a wide range of applications, especially in improving the energy efficiency of buildings. It can automatically adjust light transmittance according to ambient light, reduce energy consumption, and provide a more comfortable indoor environment. In the future, dynamic windows are expected to be used in more buildings, especially in places where precise control of light and temperature is required.

[0003] At present, metal electrodeposition dynamic windows require the transparent conductive glass electrode surface to have stability, conductive uniformity, more binding sites and free energy gain, etc. In order to achieve rapid dual-state switching in large-scale applications, the center and edge of the transparent conductive glass electrode must have good conductivity. At present, most of the modifications of transparent conductive glass in dynamic windows are based on electrochromic windows, including the use of physical coating, chemical or electrochemical polymerization, and the preparation of an electrochromic layer by coating a conductive polymer on the ITO substrate of the conductive glass. However, this coated polymer film has problems such as low mechanical strength, easy breakage, unstable hydrolysis, strong dependence on reaction conditions (such as pH, temperature, etc.), and there are also disadvantages such as weak adsorption between the polymer film and the ITO substrate, and easy detachment from the ITO substrate. The above-mentioned disadvantages reduce the stability of the polymer film in the liquid electrolyte and limit its application.

[0004] In addition, for the modification of transparent conductive glass for metal electrodeposition dynamic windows, only Strand et al. have reported so far, in which a layer of 3-mercaptopropionic acid was modified on the ITO of the conductive glass, followed by the adsorption of 3nm Pt nanoparticles. However, the prior art method for modifying conductive glass ITO has the following disadvantages: (1) It is expensive: the Pt nanoparticle product used is Sigma's 3nm platinum nanoparticle solution, which costs about 4,500 yuan per 25 ml; (2) The Pt nanoparticle solution is unstable: the platinum metal particles in the platinum nanoparticle solution used are in a suspension state. When dispersed by solvent, they will agglomerate and settle after being left for a long time, making the solution unusable, which is not conducive to commercialization; (3) The pretreatment time of this modification method is long: This technology requires ITO to be soaked in 3-mercaptopropionic acid for 24 hours and then soaked in platinum nanoparticle solution for 24 hours; (4) Since the platinum nanoparticles modified on ITO are large in size and poor in uniformity, the voltage difference between the center and the edge of the ITO modification layer is large, which is not conducive to the uniform and rapid deposition of the metal layer when applied to dynamic windows, thereby affecting the adjustment conversion of the dynamic windows. Summary of the invention

[0005] In order to overcome the shortcomings of the prior art, the first purpose of the present invention is to provide a method for preparing a conductive substance modified material layer, which can effectively reduce the voltage difference between the center and the edge of the conductive layer, and has the advantages of low material cost and avoidance of particle agglomeration problems, short preparation time, and simple and quick process.

[0006] In order to overcome the shortcomings of the prior art, the second purpose of the present invention is to provide a conductive glass electrode, which can effectively reduce the voltage difference between the center and the edge of the conductive layer, enable the metal layer to be deposited uniformly and quickly, and has low preparation cost and high preparation efficiency.

[0007] The third object of the present invention is to provide a conductive glass which can effectively reduce the voltage difference between the center and edge of the conductive layer, enable the metal layer to be deposited evenly and quickly, and has a low preparation cost. It can be well applied to the preparation of dynamic windows and has a high preparation efficiency, which is conducive to commercialization.

[0008] The fourth object of the present invention is to provide a dynamic window that is more uniform and rapid in switching between transparent and opaque states, and has low manufacturing cost and high manufacturing efficiency.

[0009] In order to achieve the first object of the above invention, the technical solution adopted by the present invention is as follows:

[0010] The present invention provides a method for preparing a conductive substance modified material layer, comprising the following steps:

[0011] S1. Plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment;

[0012] S2, silanization reaction: immersing the indium tin oxide conductive glass treated in step S1 in an acidic solution containing vinyl silane to perform a surface silanization reaction, and then washing with water and drying;

[0013] S3, polymerization reaction: immersing the indium tin oxide conductive glass that has completed the silanization reaction in step S2 in an aqueous solution containing methacryloyloxyethyl trimethyl ammonium chloride as an initiator to perform a heating polymerization reaction, and then washing with water and drying;

[0014] S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate to carry out ion exchange adsorption reaction, and then wash and dry to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer.

[0015] The invention discloses a method for preparing a conductive material modified material layer. The reaction mechanism is as follows: plasma treatment is performed on indium tin oxide conductive glass in step S1, and then hydroxyl groups (-OH) are introduced on the indium tin oxide layer to make it hydrophilic. The hydroxyl groups participate in the silanization reaction in step S2, and the surface of the indium tin oxide layer is silanized with vinyl silane in an acidic solution, and vinyl groups are introduced through the hydroxyl groups in S1; then methacryloyloxyethyl trimethyl ammonium chloride is used to perform an in-situ free radical polymerization reaction with the vinyl groups introduced by silanization, and then a polymer layer is formed on the surface of the indium tin oxide conductive glass; then an aqueous solution of ammonium tetrachloropalladate is used to perform an ion exchange reaction with the polymer layer on the surface of the indium tin oxide conductive glass, and the Cl-terminated polymer layer anchored on the conductive glass polymer layer is anchored on the conductive glass polymer layer. - Will react with [Pd(Cl) 4 ] 2- Ion exchange was performed to convert [Pd(Cl) 4 ] 2- It is adsorbed on the surface of indium tin oxide conductive glass to obtain Pd-ITO conductive glass.

[0016] The present invention discloses a method for preparing a conductive material modified material layer, wherein a polymer layer is formed on the surface of the indium tin oxide conductive glass after plasma treatment and then subjected to a silanization reaction, followed by an in-situ free radical polymerization reaction, and the palladium ions used as a catalyst are finally adsorbed by the polymer layer. Compared with the prior art in which metal particles are modified on the surface of the indium tin oxide conductive glass, the present application modifies the surface of the indium tin oxide conductive glass with palladium ions, and can form a more uniform catalyst layer on the surface of the indium tin oxide conductive glass compared with metal particles, thereby effectively reducing the voltage difference between the center and the edge of the prepared Pd-ITO conductive layer. On the other hand, since an aqueous solution of ammonium tetrachloropalladate is used when introducing a metal catalyst during the preparation process of the present application, compared with the metal particle suspension used in the prior art, the problem of metal particle agglomeration and suspension instability can be avoided, and the present application also has the advantages of low raw material cost, short preparation time, and simple and quick process.

[0017] Furthermore, in step S1, the plasma cleaning machine performs plasma treatment for 50s to 70s. The plasma treatment time can well introduce hydroxyl groups on the surface of the indium tin oxide conductive glass. The plasma cleaning machine reacts chemically with the surface of the indium tin oxide layer of the indium tin oxide conductive glass through its active particles, breaks the original chemical bonds, and introduces hydrophilic functional groups such as hydroxyl groups. The introduction of these functional groups can significantly improve the hydrophilicity of the surface of the indium tin oxide conductive glass and improve the surface wetting properties.

[0018] Furthermore, in step S2, the vinyl silane is vinyl trimethoxy silane or vinyl triethoxy silane, the solvent of the solution is ethanol, and the volume percentage of the vinyl silane in the ethanol is 0.1% to 5%; vinyl trimethoxy silane or vinyl triethoxy silane is easily soluble in ethanol and has the advantage of low material cost. In addition, vinyl trimethoxy silane or vinyl triethoxy silane bonds with the hydroxyl group on the surface of the indium tin oxide conductive glass through the hydrolysis of the methoxy group or the ethoxy group, thereby introducing vinyl groups on the surface of the indium tin oxide conductive glass.

[0019] The surface silanization reaction time is 30 minutes to 70 minutes. The surface silanization reaction time is short, but sufficient to achieve a complete silanization reaction and well introduce vinyl groups.

[0020] Furthermore, in step S2, the pH of the vinyl silane solution is adjusted to 3-4.5 using glacial acetic acid. The vinyl silane solution is adjusted to an acidic solution using glacial acetic acid, which can promote the hydrolysis of the vinyl silane during the silanization reaction, thereby bonding to the surface of the indium tin oxide conductive glass.

[0021] Furthermore, in step S3, the initiator is potassium persulfate, and the concentration of potassium persulfate in the aqueous solution is 0.1 g / L to 3 g / L; wherein the initiator potassium persulfate can well promote free radical polymerization reaction and has the advantage of low material cost.

[0022] The mass concentration of the methacryloyloxyethyl trimethyl ammonium chloride in the aqueous solution is 5wt% to 25wt%. The aqueous solution of the methacryloyloxyethyl trimethyl ammonium chloride has good solution stability and cooperates with the aqueous solution of ammonium tetrachloropalladate to well avoid the problem of particle agglomeration in the prior art.

[0023] Furthermore, in step S3, the heating temperature of the polymerization reaction is 50° C. to 90° C., and the polymerization reaction time is 20 min to 70 min. The polymerization reaction conditions are mild and the reaction time is short.

[0024] Furthermore, in step S4, the mass volume concentration of the ammonium tetrachloropalladate in the aqueous solution is 0.1 g / L to 2 g / L; the amount of the ammonium tetrachloropalladate is small, the material cost is low, and because palladium ions are adsorbed, the problem of particle agglomeration in the prior art can be avoided.

[0025] The time of the ion exchange adsorption reaction is 30 minutes to 100 minutes. The time of the ion exchange adsorption reaction is short, and the preparation has the advantage of high efficiency.

[0026] In order to achieve the second purpose of the above invention, the technical solution adopted by the present invention is as follows:

[0027] The present invention provides a conductive glass electrode. The above-mentioned method for preparing a conductive substance modified material layer is applied to prepare a conductive glass electrode, and the Pd-ITO conductive layer is used as an electrode.

[0028] The conductive glass electrode of the present invention is a Pd-ITO conductive layer, which is prepared by adsorbing palladium ions through a polymer layer and ammonium tetrachloropalladate, and can effectively reduce the voltage difference between the center and the edge of the conductive layer, and can make the metal layer deposited uniformly and quickly, and has low preparation cost and high preparation efficiency.

[0029] In order to achieve the third purpose of the above invention, the technical solution adopted by the present invention is as follows:

[0030] The present invention provides a conductive glass. The above-mentioned method for preparing a conductive substance modified material layer is applied to preparing the conductive glass.

[0031] The conductive glass of the present invention forms a polymer layer on the surface of the indium tin oxide conductive glass by subjecting the indium tin oxide conductive glass to plasma treatment, followed by a silanization reaction, and then an in-situ free radical polymerization reaction. The polymer layer finally adsorbs palladium ions as a catalyst, thereby preparing a conductive glass with a Pd-ITO conductive layer. Therefore, the conductive glass can effectively reduce the voltage difference between the center and the edge of the conductive layer, can make the metal layer uniformly and quickly deposited, and has a low preparation cost, can be well applied to the preparation of dynamic windows, and has a high preparation efficiency, which is conducive to commercialization.

[0032] In order to achieve the fourth object of the above invention, the technical solution adopted by the present invention is as follows:

[0033] The present invention provides a dynamic window, comprising conductive glass modified by the above-mentioned method for preparing a conductive substance modified material layer.

[0034] The dynamic window of the present invention can achieve more uniform and rapid conversion between transparent and opaque states because the conductive glass produced can effectively reduce the voltage difference between the center and edge of the conductive layer, allowing the metal layer to be deposited evenly and quickly. The dynamic window has low preparation cost and high preparation efficiency.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) A method for preparing a conductive material modified material layer of the present invention, wherein a polymer layer is formed on the surface of the indium tin oxide conductive glass by plasma treatment and then silanization reaction, followed by in-situ free radical polymerization reaction, and finally palladium ions as a catalyst are adsorbed by the polymer layer. Compared with the prior art that modifies the metal particles on the surface of the indium tin oxide conductive glass, the present application modifies the surface of the indium tin oxide conductive glass with palladium ions, which can form a more uniform catalyst layer on the surface of the indium tin oxide conductive glass compared with the metal particles, thereby effectively reducing the voltage difference between the center and the edge of the prepared Pd-ITO conductive layer. On the other hand, since the aqueous solution of ammonium tetrachloropalladate is used when introducing the metal catalyst in the preparation process of the present application, compared with the metal particle suspension used in the prior art, the problem of metal particle agglomeration and suspension instability can be avoided, and the present application also has the advantages of low raw material cost, short preparation time, and simple and quick process.

[0037] (2) The method for preparing a conductive material modified material layer of the present invention is cheaper than the platinum nanoparticle solution used in the prior art. The price of the ammonium tetrachloropalladate solution used in the present invention is about 180 yuan per 250 mg, and the concentration of each use is 1g / L, and the amount used is 20ml. Therefore, under the same conditions, the price per use is about 15 yuan, which can greatly reduce the cost of applying and preparing dynamic windows.

[0038] (3) The preparation method of a conductive material modified material layer of the present invention only requires four preparation steps, and the preparation time of the entire preparation process can be controlled within 3 hours. Compared with the preparation time of more than 48 hours in the prior art, the present application has the advantage of short preparation time, which can greatly improve the preparation efficiency and is conducive to commercial application. In addition, the entire preparation process is simple and convenient, and can be produced in large quantities and quickly without complicated operation processes.

[0039] (4) The conductive glass electrode of the present invention is a Pd-ITO conductive layer, which is obtained by adsorbing palladium ions through a polymer layer and ammonium tetrachloropalladate. It can effectively reduce the voltage difference between the center and the edge of the conductive layer, and can make the metal layer deposited uniformly and quickly. It has low preparation cost and high preparation efficiency.

[0040] (5) A conductive glass of the present invention forms a polymer layer on the surface of the indium tin oxide conductive glass by subjecting the indium tin oxide conductive glass to plasma treatment, followed by a silanization reaction, and then an in-situ free radical polymerization reaction. The polymer layer finally adsorbs palladium ions as a catalyst to obtain a conductive glass having a Pd-ITO conductive layer. Therefore, the conductive glass can effectively reduce the voltage difference between the center and the edge of the conductive layer, and can make the metal layer deposited uniformly and quickly. The preparation cost is low, and the glass can be well applied to the preparation of dynamic windows. The preparation efficiency is high, and the glass is conducive to commercialization.

[0041] (6) The dynamic window of the present invention can achieve a more uniform and rapid transition between transparent and opaque states because the conductive glass produced can effectively reduce the voltage difference between the center and edge of the conductive layer, allowing the metal layer to be deposited evenly and quickly. The dynamic window has a low production cost and high production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 It is a schematic diagram of the preparation process of Example 1 of the present invention.

[0044] Figure 2 It is a graph showing the copper deposition and adhesion test of Example 1, Comparative Example 1 and an indium tin oxide conductive glass sample that has not undergone any treatment.

[0045] Figure 3 It is a schematic diagram of the structure of a device assembled with conductive glass having a Pd-ITO conductive layer prepared in Example 1.

[0046] Figure 4 It is the transmittance of unmodified ITO conductive glass after copper deposition at the center and edge for 180s.

[0047] Figure 5 It is the transmittance of the Pd-ITO conductive glass of Example 1 after copper deposition at the center and edge for 180 seconds. DETAILED DESCRIPTION

[0048] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0049] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. In the present invention, the singular forms "a", "said" and "the" used in the embodiments and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0050] In the present invention, the code ITO refers to indium tin oxide.

[0051] In an embodiment of the present invention, a method for preparing a conductive substance modified material layer comprises the following steps:

[0052] S1. Plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment;

[0053] S2, silanization reaction: immersing the indium tin oxide conductive glass treated in step S1 in an acidic solution containing vinyl silane to perform a surface silanization reaction, and then washing with water and drying;

[0054] S3, polymerization reaction: immersing the indium tin oxide conductive glass that has completed the silanization reaction in step S2 in an aqueous solution containing methacryloyloxyethyl trimethyl ammonium chloride as an initiator to perform a heating polymerization reaction, and then washing with water and drying;

[0055] S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate to carry out ion exchange adsorption reaction, and then wash and dry to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer.

[0056] A method for preparing a conductive material modified material layer in the embodiment, the reaction mechanism is: plasma treatment is performed on the indium tin oxide conductive glass in step S1, and then hydroxyl groups (-OH) are introduced on the indium tin oxide layer to make it hydrophilic, and the hydroxyl groups participate in the silanization reaction in step S2, and the surface of the indium tin oxide layer is silanized with vinyl silane in an acidic solution, and vinyl groups are introduced through the hydroxyl groups in S1; then methacryloyloxyethyl trimethyl ammonium chloride and the vinyl groups introduced by silanization are subjected to in-situ free radical polymerization reaction, and then a polymer layer is formed on the surface of the indium tin oxide conductive glass; then an aqueous solution of ammonium tetrachloropalladate is subjected to an ion exchange reaction with the polymer layer on the surface of the indium tin oxide conductive glass, and Cl anchored on the polymer layer of the conductive glass - Will react with [Pd(Cl) 4 ] 2- Ion exchange was performed to convert [Pd(Cl) 4 ] 2- It is adsorbed on the surface of indium tin oxide conductive glass to obtain Pd-ITO conductive glass.

[0057] A method for preparing a conductive material modified material layer in the embodiment, by plasma-treating indium tin oxide conductive glass and then performing a silanization reaction, followed by an in-situ free radical polymerization reaction, a polymer layer is formed on the surface of the indium tin oxide conductive glass, and palladium ions as a catalyst are finally adsorbed by the polymer layer. Compared with the prior art that modifies the metal particles on the surface of indium tin oxide conductive glass, the present application modifies the surface of indium tin oxide conductive glass with palladium ions, which can form a more uniform catalyst layer on the surface of indium tin oxide conductive glass compared with metal particles, thereby effectively reducing the voltage difference between the center and edge of the prepared Pd-ITO conductive layer. On the other hand, since an aqueous solution of ammonium tetrachloropalladate is used when introducing a metal catalyst in the preparation process of the present application, compared with the metal particle suspension used in the prior art, the problem of metal particle agglomeration and suspension instability can be avoided, and the present application also has the advantages of low raw material cost, short preparation time, and simple and quick process.

[0058] In some embodiments, in step S1, the plasma cleaning machine performs plasma treatment for 50s to 70s. The plasma treatment time can well introduce hydroxyl groups on the surface of the indium tin oxide conductive glass. The plasma cleaning machine reacts chemically with the surface of the indium tin oxide layer of the indium tin oxide conductive glass through its active particles, breaks the original chemical bonds, and introduces hydrophilic functional groups such as hydroxyl groups. The introduction of these functional groups can significantly improve the hydrophilicity of the surface of the indium tin oxide conductive glass and improve the wetting properties of the surface.

[0059] In some embodiments, in step S2, the vinyl silane is vinyl trimethoxy silane or vinyl triethoxy silane, the solvent of the solution is ethanol, and the volume percentage of the vinyl silane in the ethanol is 0.1% to 5%; vinyl trimethoxy silane or vinyl triethoxy silane is easily soluble in ethanol and has the advantage of low material cost. In addition, vinyl trimethoxy silane or vinyl triethoxy silane bonds with the hydroxyl group on the surface of the indium tin oxide conductive glass through the hydrolysis of the methoxy group or the ethoxy group, thereby introducing a vinyl group on the surface of the indium tin oxide conductive glass.

[0060] The surface silanization reaction time is 30 minutes to 70 minutes. The surface silanization reaction time is short, but sufficient to achieve a complete silanization reaction and well introduce vinyl groups.

[0061] In some embodiments, in step S2, the pH of the vinyl silane solution is adjusted to 3-4.5 using glacial acetic acid. The vinyl silane solution is adjusted to an acidic solution using glacial acetic acid, which can promote the hydrolysis of the vinyl silane during the silanization reaction, thereby bonding to the surface of the indium tin oxide conductive glass.

[0062] In some embodiments, in step S3, the initiator is potassium persulfate, and the concentration of potassium persulfate in the aqueous solution is 0.1 g / L to 3 g / L; wherein the initiator potassium persulfate can well promote free radical polymerization reaction and has the advantage of low material cost.

[0063] The mass concentration of the methacryloyloxyethyl trimethyl ammonium chloride in the aqueous solution is 5wt% to 25wt%. The aqueous solution of the methacryloyloxyethyl trimethyl ammonium chloride has good solution stability and cooperates with the aqueous solution of ammonium tetrachloropalladate to well avoid the problem of particle agglomeration in the prior art.

[0064] In some embodiments, in step S3, the heating temperature of the polymerization reaction is 50° C. to 90° C., and the polymerization reaction time is 20 min to 70 min. The polymerization reaction conditions are mild and the reaction time is short.

[0065] In some embodiments, in step S4, the mass volume concentration of the ammonium tetrachloropalladate in the aqueous solution is 0.1 g / L to 2 g / L; the amount of ammonium tetrachloropalladate used is small, the material cost is low, and because palladium ions are adsorbed, the problem of particle agglomeration in the prior art can be avoided.

[0066] The time of the ion exchange adsorption reaction is 30 minutes to 100 minutes. The time of the ion exchange adsorption reaction is short, and the preparation has the advantage of high efficiency.

[0067] In an embodiment of the present invention, a conductive glass electrode is provided. The above-mentioned method for preparing a conductive substance modified material layer is applied to prepare a conductive glass electrode, and the Pd-ITO conductive layer is used as an electrode.

[0068] A conductive glass electrode in the embodiment, since the electrode is a Pd-ITO conductive layer, is prepared by adsorbing palladium ions through a polymer layer and ammonium tetrachloropalladate, can effectively reduce the voltage difference between the center and the edge of the conductive layer, can make the metal layer deposited uniformly and quickly, and has low preparation cost and high preparation efficiency.

[0069] In an embodiment of the present invention, a conductive glass is provided, and the above-mentioned method for preparing a conductive substance modified material layer is applied to prepare the conductive glass.

[0070] A conductive glass in the embodiment, by subjecting indium tin oxide conductive glass to plasma treatment, followed by silanization reaction, and then performing an in-situ free radical polymerization reaction, a polymer layer is formed on the surface of the indium tin oxide conductive glass, and palladium ions as a catalyst are finally adsorbed by the polymer layer to obtain a conductive glass with a Pd-ITO conductive layer. Therefore, the conductive glass can effectively reduce the voltage difference between the center and the edge of the conductive layer, and can make the metal layer uniformly and quickly deposited, and has a low preparation cost, can be well applied to the preparation of dynamic windows, and has a high preparation efficiency, which is conducive to commercialization.

[0071] In an embodiment of the present invention, a dynamic window includes conductive glass modified by the above-mentioned method for preparing a conductive substance modified material layer.

[0072] A dynamic window in the embodiment, because the conductive glass produced can effectively reduce the voltage difference between the center and the edge of the conductive layer, the metal layer can be deposited evenly and quickly. Therefore, the dynamic window is more uniform and rapid in realizing the transition between transparent and opaque states, and has low preparation cost and high preparation efficiency.

[0073] The following describes the invention in conjunction with specific embodiments.

[0074] Example 1

[0075] A method for preparing a conductive substance modified material layer comprises the following steps:

[0076] S1. Plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment for 60 seconds;

[0077] S2, silanization reaction: soak the indium tin oxide conductive glass treated in step S1 in an ethanol solution containing vinyl trimethoxysilane, add glacial acetic acid to adjust the pH to 3, and then perform surface silanization reaction for 30 minutes, and then wash and dry the indium tin oxide conductive glass after the silanization reaction; in this embodiment, the volume percentage of vinyl trimethoxysilane in ethanol is 5%;

[0078] S3, polymerization reaction: the indium tin oxide conductive glass that has completed the silanization reaction in step S2 is immersed in an aqueous solution of methacryloyloxyethyl trimethyl ammonium chloride containing an initiator of potassium persulfate, heated to 50°C for polymerization reaction for 70 minutes, and then washed with water and dried with nitrogen; in this embodiment, the concentration of potassium persulfate in the aqueous solution is 3g / L; the mass concentration of methacryloyloxyethyl trimethyl ammonium chloride in the aqueous solution is 25wt%;

[0079] S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate, perform ion exchange adsorption reaction for 100 minutes, then wash with water and blow dry with nitrogen to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer. In this embodiment, the mass volume concentration of ammonium tetrachloropalladate in the aqueous solution is 0.6g / L.

[0080] Example 2

[0081] A method for preparing a conductive substance modified material layer comprises the following steps:

[0082] S1, plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment for 50 seconds;

[0083] S2, silanization reaction: soak the indium tin oxide conductive glass treated in step S1 in an ethanol solution containing vinyl triethoxysilane, add glacial acetic acid to adjust the pH to 3.5, and then perform surface silanization reaction for 45 minutes, and then wash and dry the indium tin oxide conductive glass after the silanization reaction; in this embodiment, the volume percentage of vinyl triethoxysilane to ethanol is 4%;

[0084] S3, polymerization reaction: immersing the indium tin oxide conductive glass that has completed the silanization reaction in step S2 in an aqueous solution of methacryloyloxyethyl trimethyl ammonium chloride containing an initiator of potassium persulfate, heating it to 60° C. for polymerization reaction for 60 min, and then washing it with water and drying it with nitrogen; in this embodiment, the concentration of potassium persulfate in the aqueous solution is 2.5 g / L; the mass concentration of methacryloyloxyethyl trimethyl ammonium chloride in the aqueous solution is 15 wt%;

[0085] S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate, perform ion exchange adsorption reaction for 80 minutes, then wash with water and blow dry with nitrogen to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer. In this embodiment, the mass volume concentration of ammonium tetrachloropalladate in the aqueous solution is 0.8g / L.

[0086] Example 3

[0087] A method for preparing a conductive substance modified material layer comprises the following steps:

[0088] S1, plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment for 70 seconds;

[0089] S2, silanization reaction: soak the indium tin oxide conductive glass treated in step S1 in an ethanol solution containing vinyl trimethoxysilane, add glacial acetic acid to adjust the pH to 3.8, and then perform surface silanization reaction for 40 minutes, and then wash and dry the indium tin oxide conductive glass after the silanization reaction; in this embodiment, the volume percentage of vinyl trimethoxysilane to ethanol is 3%;

[0090] S3, polymerization reaction: immersing the indium tin oxide conductive glass that has completed the silanization reaction in step S2 in an aqueous solution of methacryloyloxyethyl trimethyl ammonium chloride containing an initiator of potassium persulfate, heating it to 70°C for polymerization reaction for 30 minutes, and then washing with water and drying it with nitrogen; in this embodiment, the concentration of potassium persulfate in the aqueous solution is 2 g / L; the mass concentration of methacryloyloxyethyl trimethyl ammonium chloride in the aqueous solution is 20wt%;

[0091] S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate, perform ion exchange adsorption reaction for 30 minutes, then wash with water and blow dry with nitrogen to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer. In this embodiment, the mass volume concentration of ammonium tetrachloropalladate in the aqueous solution is 2g / L.

[0092] Example 4

[0093] A method for preparing a conductive substance modified material layer comprises the following steps:

[0094] S1, plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment for 55 seconds;

[0095] S2, silanization reaction: soak the indium tin oxide conductive glass treated in step S1 in an ethanol solution containing vinyl trimethoxysilane, add glacial acetic acid to adjust the pH to 4, and then perform surface silanization reaction for 70 minutes, and then wash and dry the indium tin oxide conductive glass after the silanization reaction; in this embodiment, the volume percentage of vinyl trimethoxysilane in ethanol is 2.5%;

[0096] S3, polymerization reaction: the indium tin oxide conductive glass that has completed the silanization reaction in step S2 is immersed in an aqueous solution of methacryloyloxyethyl trimethyl ammonium chloride containing an initiator of potassium persulfate, heated to 90°C for polymerization reaction for 20 minutes, and then washed with water and dried with nitrogen; in this embodiment, the concentration of potassium persulfate in the aqueous solution is 1.5 g / L; the mass concentration of methacryloyloxyethyl trimethyl ammonium chloride in the aqueous solution is 5wt%;

[0097] S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate, perform ion exchange adsorption reaction for 90 minutes, then wash with water and blow dry with nitrogen to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer. In this embodiment, the mass volume concentration of ammonium tetrachloropalladate in the aqueous solution is 0.5g / L.

[0098] Example 5

[0099] A method for preparing a conductive substance modified material layer comprises the following steps:

[0100] S1, plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment for 65 seconds;

[0101] S2, silanization reaction: soaking the indium tin oxide conductive glass treated in step S1 in an ethanol solution containing vinyl trimethoxysilane, adding glacial acetic acid to adjust the pH to 4.5, and then performing a surface silanization reaction for 60 minutes, and then washing and drying the indium tin oxide conductive glass after the silanization reaction; in this embodiment, the volume percentage of vinyl trimethoxysilane in ethanol is 0.1%;

[0102] S3, polymerization reaction: the indium tin oxide conductive glass that has completed the silanization reaction in step S2 is immersed in an aqueous solution of methacryloyloxyethyl trimethyl ammonium chloride containing an initiator of potassium persulfate, heated to 80°C for polymerization reaction for 30 minutes, and then washed with water and dried with nitrogen; in this embodiment, the concentration of potassium persulfate in the aqueous solution is 0.1 g / L; the mass concentration of methacryloyloxyethyl trimethyl ammonium chloride in the aqueous solution is 10wt%;

[0103] S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate, perform ion exchange adsorption reaction for 100 minutes, then wash with water and blow dry with nitrogen to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer. In this embodiment, the mass volume concentration of ammonium tetrachloropalladate in the aqueous solution is 0.1g / L.

[0104] Example 6

[0105] A conductive glass electrode, wherein the preparation method of any one of the conductive substance modified material layers of embodiments 1 to 5 is applied to prepare a conductive glass electrode, wherein the Pd-ITO conductive layer is used as an electrode.

[0106] Example 7

[0107] A conductive glass, wherein the preparation method of any one of embodiments 1 to 5 of the conductive substance modified material layer is applied to prepare the conductive glass.

[0108] Example 8

[0109] A dynamic window comprises conductive glass modified by the preparation method of a conductive substance modified material layer according to any one of embodiments 1 to 5.

[0110] Comparative Example 1

[0111] A method for preparing a conductive substance modified material layer. The difference between this comparative example and Example 1 is that this comparative example omits steps S1, S2 and S3 of Example 1, and directly immerses the indium tin oxide conductive glass in an aqueous solution of ammonium tetrachloropalladate. The remaining steps and condition parameters are the same as step S4 of Example 1.

[0112] Experimental testing

[0113] (I) Copper deposition test

[0114] The indium tin oxide conductive glass without any treatment, the conductive glass with Pd-ITO conductive layer prepared in Example 1, and the conductive glass prepared in Comparative Example 1 were used as three samples, and copper deposition experiments were performed respectively. The experimental detection method is as follows:

[0115] First, prepare the plating solution: 0.1 M copper sulfate, 0.2 M potassium sodium tartrate, 0.1 M formaldehyde, and adjust the pH value to 12 with sodium hydroxide.

[0116] Then, the three samples prepared above were immersed in the plating solution respectively, reacted at 40°C for 2 minutes, and then the three samples were taken out, rinsed with deionized water, and blown dry with nitrogen, and then the surface of the conductive glass was observed to see if there was copper deposition. Among them, the copper deposition results are as follows Figure 2 shown.

[0117] Figure 2 Among them, sample 1 is a sample of "indium tin oxide conductive glass without any treatment", sample 2 is a sample of "conductive glass prepared in comparative example 1", and sample 3 is a sample of "conductive glass with Pd-ITO conductive layer prepared in example 1".

[0118] from Figure 2 From the experimental results of copper deposition, it can be seen that sample 1 of "indium tin oxide conductive glass without any treatment" will not deposit copper, "conductive glass prepared in comparative example 1" deposits a small amount of copper, and "conductive glass with Pd-ITO conductive layer prepared in example 1" deposits an obvious copper layer, and the uniformity of the copper layer is very good.

[0119] Therefore, it can be seen that the indium tin oxide conductive glass in Comparative Example 1, which has not undergone plasma treatment, silanization reaction and polymerization reaction, can only be modified with a small amount of Pd ions when directly immersed in an aqueous solution of ammonium tetrachloropalladate, and the Pd ions are uneven, resulting in a small amount of and uneven copper deposition. However, the indium tin oxide conductive glass of Example 1 can be uniformly modified with a large amount of Pd ions because it is sequentially subjected to plasma treatment, silanization reaction and polymerization reaction and then immersed in an aqueous solution of ammonium tetrachloropalladate, and can thus uniformly deposit a large amount of copper layers.

[0120] (II) Adhesion test of copper deposit layer

[0121] The conductive glass with the Pd-ITO conductive layer prepared in Example 1 and the conductive glass prepared in Comparative Example 1 were used as two samples, and copper deposition experiments were performed respectively, and the adhesion of the deposited copper layers was tested.

[0122] The adhesion test is as follows: cut a 3M tape of appropriate length, stick it on the copper surface of the two samples, scrape it flat so that the tape fits tightly to the copper surface, then tear it off and observe. Figure 2 shown.

[0123] Depend on Figure 2 It can be seen that the copper deposited layer in the sample of Comparative Example 1 will be stuck to the 3M tape, while the copper deposited layer in the sample of Example 1 will not be stuck to the 3M tape, which shows that the Pd-ITO conductive layer prepared after plasma treatment, silanization reaction and polymerization reaction in Example 1 can make the copper deposited layer have better adhesion.

[0124] (III) Transmittance, center and edge metal deposition rate detection

[0125] The unmodified indium tin oxide conductive glass (hereinafter referred to as "sample 1") and the conductive glass with a Pd-ITO conductive layer prepared in Example 1 (hereinafter referred to as "sample 2") were tested for transmittance at the center and edge to detect the sedimentation rate at the center and edge. The specific test experiment is as follows:

[0126] Preparation of the plating solution: prepare an aqueous solution of 15 mM copper chloride, 5 mM bismuth chloride, 10 mM hydrochloric acid and 1 M lithium bromide, add 0.1 wt % polyvinyl alcohol, and heat and stir at 80° C. overnight.

[0127] Device assembly: Paste a circle of copper conductive tape around the working electrode ITO of sample 1 and the working electrode Pd-ITO of sample 2, and extend a conductive tape to pass electricity, and then paste a layer of polyimide tape on the copper conductive tape; use Kraft glue to stick the working electrode to the device frame to prevent leakage; use ordinary glass and copper metal frames of the same size as the counter electrode and reference electrode on the other side, and use Kraft glue to stick the two to the device frame to prevent leakage. Figure 3 , which is a schematic diagram of the structure of a device assembled with conductive glass having a Pd-ITO conductive layer prepared in Example 1.

[0128] Transmittance test: This experiment uses 50*50mm glass; the Japanese SHIMADZU ultraviolet-visible-near-infrared spectrophotometer model UV-3600plus is used for transmittance test; the quartz crystal microbalance model CHI440C of Shanghai Chenhua Instrument Co., Ltd. is used to provide constant voltage; the plating solution is injected into the prepared device, and after sealing, the real-time transmittance is tested under the ultraviolet-visible-near-infrared spectrophotometer, and the CHI440C is set to provide a constant voltage of -0.6V to test the center and edge metal deposition rate of the device within 180s.

[0129] like Figure 4 As shown in the figure, the transmittance of the unmodified ITO conductive glass after copper deposition for 180s at the center and edge shows that the metal deposition speed of the unmodified ITO conductive glass is slow, especially at the center, the transmittance of the conductive glass is still 50% after 180s of sedimentation, indicating that the metal deposition effect of the unmodified ITO conductive glass is poor, and it is difficult to achieve the transition between transparent and opaque states. In addition, the voltage difference between the center and the edge is relatively large, which leads to a large difference in the sedimentation rate at the center and the edge. Therefore, the unmodified ITO conductive glass cannot deposit the metal evenly and quickly.

[0130] like Figure 5As shown in the figure, the transmittance of the conductive glass with Pd-ITO conductive layer prepared in Example 1 after copper deposition for 180s at the center and edge shows that the metal deposition speed of the Pd-ITO conductive glass prepared in Example 1 is fast, and the transmittance of the conductive glass is close to 0% when the sedimentation is 180s at the center or the edge, indicating that the metal deposition effect of the Pd-ITO conductive glass prepared in Example 1 is good, and the transparent and opaque state conversion can be well achieved. And the voltage difference at the center and the edge is greatly reduced, so that the sedimentation rate at the center and the edge is consistent, therefore, the Pd-ITO conductive glass prepared in Example 1 can well make the metal uniform and fast deposition.

[0131] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a conductive substance modified material layer, characterized in that: The following steps are involved: S1. Plasma treatment: placing the indium tin oxide conductive glass in a plasma cleaning machine for plasma treatment; S2, silanization reaction: immersing the indium tin oxide conductive glass treated in step S1 in an acidic solution containing vinyl silane to perform a surface silanization reaction, and then washing with water and drying; S3, polymerization reaction: immersing the indium tin oxide conductive glass that has completed the silanization reaction in step S2 in an aqueous solution containing methacryloyloxyethyl trimethyl ammonium chloride as an initiator to perform a heating polymerization reaction, and then washing with water and drying; S4, preparation of Pd-ITO conductive layer: immerse the indium tin oxide conductive glass that has completed the polymerization reaction in step S3 in an aqueous solution of ammonium tetrachloropalladate to carry out ion exchange adsorption reaction, and then wash and dry to obtain a Pd-ITO conductive layer, that is, complete the preparation of the conductive substance modified material layer.

2. The method for preparing a conductive substance modified material layer according to claim 1, characterized in that: In the step S1, the plasma cleaning machine performs plasma treatment for 50s to 70s.

3. The method for preparing a conductive substance modified material layer according to claim 1, characterized in that: In step S2, the vinyl silane is vinyl trimethoxy silane or vinyl triethoxy silane, the solvent of the solution is ethanol, and the volume percentage of the vinyl silane to the ethanol is 0.1% to 5%; The surface silanization reaction time is 30 min to 70 min.

4. The method for preparing a conductive substance modified material layer according to claim 1, characterized in that: In the step S2, the pH of the vinyl silane solution is adjusted to 3-4.5 using glacial acetic acid.

5. The method for preparing a conductive substance modified material layer according to claim 1, characterized in that: In step S3, the initiator is potassium persulfate, and the concentration of potassium persulfate in the aqueous solution is 0.1 g / L to 3 g / L; The mass concentration of the methacryloyloxyethyltrimethylammonium chloride in the aqueous solution is 5wt% to 25wt%.

6. The method for preparing a conductive substance modified material layer according to claim 1, characterized in that: In the step S3, the heating temperature of the polymerization reaction is 50° C. to 90° C., and the time of the polymerization reaction is 20 min to 70 min.

7. The method for preparing a conductive substance modified material layer according to claim 1, characterized in that: In the step S4, the mass volume concentration of the ammonium tetrachloropalladate in the aqueous solution is 0.1 g / L to 2 g / L; The time of the ion exchange adsorption reaction is 30 minutes to 100 minutes.

8. A conductive glass electrode, characterized in that: The method for preparing a conductive substance modified material layer as described in any one of claims 1 to 7 is applied to prepare a conductive glass electrode, and the Pd-ITO conductive layer is used as an electrode.

9. A conductive glass, characterized in that: The method for preparing a conductive substance modified material layer as described in any one of claims 1 to 7 is applied to prepare conductive glass.

10. A dynamic window, characterized in that: The conductive glass is prepared by modification according to the method for preparing a conductive substance modified material layer as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Metal modified carbon fiber and preparation method thereof

    CN106758173A

  • Photoelectrochemical (PEC) sensor for detecting kanamycin (KAN), and preparation method application of PEC sensor for detecting KAN

    CN110514603A

  • Photovoltaic self-driven flexible gas sensor based on organic-inorganic heterojunction and preparation method of photovoltaic self-driven flexible gas senso

    CN111505062A

  • Electrochromic device based on transparent metal mesh electrode

    CN113608391A

  • Electrically regulated visible-near infrared-middle and far infrared device and preparation method thereof

    CN116382007A